Non-Audit Services, Audit Firm Tenure and Earnings Management in Malaysia - Hasan Mohammed Bamahros; Wan Nordin Wan-Hussin (Asian Academy of Management Journal of Accounting and Finance, 2015)
The main objective of this study is to investigate the association of auditor-provided non-audit services and audit firm tenure with earnings management in Malaysian public listed firms. Two measurements, namely, discretionary current accruals based on the performance-adjusted model developed by Ashbaugh, LaFond and Mayhew (2003) and discretionary total accruals based on the modified Jones model (1991), are employed to estimate the level of earnings management. Our sample consists of 525 companies for financial year 2009. The results suggest that longer audit firm tenure reduces earnings management. However, the magnitude of non-audit fees exacerbates earnings management. Based on the empirical evidence, any attempt to legislate audit firm rotation in Malaysia is unwarranted. Further research is required to move toward a policy resolution on the restriction of non-audit services in Malaysia.